Water Resources and Farming Systems under Krishna River Sub-basin between Nagarjuna Sagar and Prakasham Barrage, Andhra Pradesh, India - Kumari, R. Vijaya; Reddy, M. Devender; Binderban, Prem (International Journal of Bio-resource and Stress Management, 2023)
A study was undertaken in Krishna river sub-basin (between Nagarjuna Sagar and Prakasham barrage) with an objective to assess the current farming systems and opportunities to introduce alternative farming systems. The sub-basin covers 192 mandals in 17 revenue divisions of seven districts, i.e. Mahaboobnagar, Khammam, Nalgonda, Warangal, Rangareddy, Krishna and Guntur. Survey was conducted in 27 mandals across 16 revenue divisions covering 135 farmers. The size of the land holding differed with source of irrigation. The size of the land holding was greater under rain-fed situation followed by canals and tube wells. The predominant cropping situations observed are paddy-paddy sequence under canal irrigation in black soils (22.2%). It was followed by cotton under rain-fed situation (21.5%) and paddy-paddy sequence (12.6%) under tube well. According to source of irrigation, cotton was predominant under rain-fed conditions (36.3%) followed by paddy-paddy sequence under canal irrigation and tube wells (25.9%). Higher gross and net returns were obtained by growing chili under different irrigation sources followed by sugarcane, cabbage and cotton. The farming system returns were higher wherever they were under canal + tube well or open wells. The returns were higher with agriculture + dairy + goat/sheep with open wells + tube wells + canal followed by agriculture and dairy with tube well, canal and rain-fed. The average annual income of large farmers was higher in Guntur district (` 2,77,748) followed by Khammam and Krishna districts. It was mainly contributed by agricultural crops and sheep and goat rearing. It can be concluded that the adoption of agriculture with diary and sheep or goat rearing under irrigation will be more remunerative than agriculture alone.